1991
DOI: 10.1584/jpestics.16.435
|View full text |Cite
|
Sign up to set email alerts
|

Competition by Auxin-Type Herbicides for NAA Binding to Maize Auxin Binding Protein

Abstract: Binding of auxin-type herbicides to maize membrane-bound auxin binding protein was compared with their physiological activities.There was a good correlation between the binding and the growth promoting activity of the herbicides, but the ethylene production or the inhibition of shoot growth did not completely correlate with the binding. Benazolin[4-chloro-2-oxobenzothiazolin-3-yl-acetic acid] did not bind to maize auxin binding protein, but it stimulated ethylene production.Quinclorac [3, 7-dichloro-8-quinolin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…However, it is a known phenomenon that different structural types of auxin analogs can show different or additional effects dependent on (1) their biokinetic properties and concentration at the site of action, (2) differentially affected signal transduction pathways leading to gene activation (Mito and Bennett 1995), and (3) the plant species and age (Coupland 1994;Sterling and Hall 1997). In contrast to IAA and 2,4-0, quinclorac did not show interaction with a putative auxin-binding protein of maize (Mito et al 1991;Sunohara and Matsumoto 1997), effects on proton excretion by mung bean hypocotyl sections (Mito et al 1990), and changes in membrane potential in barnyardgrass coleoptiles and elongation growth of oat (Avma sativa L.) coleoptiles (N. Lopez-Martinez et al, personal communication). However, this is not necessarily a negative indication because structure-activity relationships of auxins between their affinity for putative binding proteins and physiological action have not hitherto always correlated well (Sterling and Hall 1997).…”
Section: Physiological and Biochemical Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is a known phenomenon that different structural types of auxin analogs can show different or additional effects dependent on (1) their biokinetic properties and concentration at the site of action, (2) differentially affected signal transduction pathways leading to gene activation (Mito and Bennett 1995), and (3) the plant species and age (Coupland 1994;Sterling and Hall 1997). In contrast to IAA and 2,4-0, quinclorac did not show interaction with a putative auxin-binding protein of maize (Mito et al 1991;Sunohara and Matsumoto 1997), effects on proton excretion by mung bean hypocotyl sections (Mito et al 1990), and changes in membrane potential in barnyardgrass coleoptiles and elongation growth of oat (Avma sativa L.) coleoptiles (N. Lopez-Martinez et al, personal communication). However, this is not necessarily a negative indication because structure-activity relationships of auxins between their affinity for putative binding proteins and physiological action have not hitherto always correlated well (Sterling and Hall 1997).…”
Section: Physiological and Biochemical Effectsmentioning
confidence: 99%
“…However, this is not necessarily a negative indication because structure-activity relationships of auxins between their affinity for putative binding proteins and physiological action have not hitherto always correlated well (Sterling and Hall 1997). Similarly, the activity of dicamba in the test for promoting proton excretion was weak (Mito et al 1991).…”
Section: Physiological and Biochemical Effectsmentioning
confidence: 99%
“…These activities can be detected rapidly (within 5-15 min after treatment) and are considered to be indicators of auxin action. Numerous studies have shown that auxinic herbicides such as 2,4-D, 3,6-dichloro-2-methoxybenzoic acid, and 4-amino-3,5,6-trichloro-2-pyridinecarboxylic acid compete with IAA for binding to an auxin receptor on the plasma membrane (Mito et al, 1991), increase nucleic acid levels (Malhorta and Hanson, 1970;Arnold and Nalewaja, 1971;Chen et al, Plant Physiol. Vol.…”
Section: -9379mentioning
confidence: 99%
“…11 2, 19961972), stimulate respiration (Koo et al, 1991b), and/or acidify the growth medium (Mito et al, 1990b). However, quinclorac neither binds to the putative auxin-binding protein of maize (Zea mays) (Mito et al, 1991) nor acidifies the growth medium of mung bean tissues (Mito et al, 1990b). Furthermore, quinclorac does not increase RNA content or respiration rates in barnyardgrass (Koo et al, 1991b).…”
Section: -9379mentioning
confidence: 99%
“…In corn plants (Zea mays), it was observed that quinclorac did not bind to ABP1 (Mito et al, 1991). Also, quinclorac did not acidify the growth medium of mung bean (Vigna radiata) tissues (Mito et al, 1990).…”
Section: Auxinic Effect (Including the Production Of Cyanate)mentioning
confidence: 99%